2022
DOI: 10.3390/nano12244436
|View full text |Cite
|
Sign up to set email alerts
|

Non-Additive Optical Response in Transition Metal Dichalcogenides Heterostructures

Abstract: Van der Waals (vdW) heterostructures pave the way to achieve the desired material properties for a variety of applications. In this way, new scientific and industrial challenges and fundamental questions arise. One of them is whether vdW materials preserve their original optical response when assembled in a heterostructure. Here, we resolve this issue for four exemplary monolayer heterostructures: MoS2/Gr, MoS2/hBN, WS2/Gr, and WS2/hBN. Through joint Raman, ellipsometry, and reflectance spectroscopies, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…However, industrial implementation requires standardized optical responses, i.e., sample-to-sample variations in optical properties should be very low. By contrast, the optical constants of vdW materials depend on numerous factors [22][23][24][25][26], among which the most influential are the dielectric environment and the synthesis method. For example, recent research [23] has demonstrated that optical constants vary dramatically among differently synthesized samples of monolayer MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, industrial implementation requires standardized optical responses, i.e., sample-to-sample variations in optical properties should be very low. By contrast, the optical constants of vdW materials depend on numerous factors [22][23][24][25][26], among which the most influential are the dielectric environment and the synthesis method. For example, recent research [23] has demonstrated that optical constants vary dramatically among differently synthesized samples of monolayer MoS 2 .…”
Section: Introductionmentioning
confidence: 99%